Hubungan Pola Makan, Asupan Kebisaan Makan, Dan Aktifitas Fisik Terhadap Kejadian Obesitas Pada Anak Sekolah Dasar : Literature Review - Nuridayanah Fadilah; Linda Riski Sefrina (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2022)
Obesity is an excessive accumulation of fat in adipose tissue caused by an imbalance between the amount of energy that enters and that is expended by the body. Obesity criteria for children aged 6-12 years is with a Z-score BMI/U > + 2 SD. Based on Riskesdas data in 2018, the prevalence of obesity in children increased rapidly to 31.0%. The factors that cause obesity in children are genetics, diet, socioeconomic status of the family, and physical activity. The purpose to determine the relationship between consumption patterns, intake of eating habits, and physical activity on the incidence of obesity in elementary school children. The method used in the study used a literature review design. The results of the analysis from the literature review found that there was a significant relationship between eating patterns, intake of eating habits, and physical activity on the incidence of obesity in elementary school children in several cities in Indonesia. Conclusion rating patterns with less frequency of eating plus the number of portions for each large meal, as well as intake of eating habits that are not in accordance with balanced nutrition guidelines, and children's lack of physical activity are risk factors for obesity in elementary school children.   Keywords: obesity; Comsumption Pattern;  food intake; physical activity; primary school children